Prevalence of Theileria annulata infection in cattle in different regions and farming systems in Algeria - Messaoudi, Z; Weir, W; Saidi, F; Kelanemer, R; Medrouh, B; Gomes, J; Bilgic, HB; Karagenc, T; Hacilarlioglu, S; Ziam, H (Journal of the Hellenic Veterinary Medical Society, 2025)
Tropical theileriosis (TT) is a tick-borne disease of cattle caused by the apicomplexan parasite Theileria annulata. It poses a major threat to the health of imported exotic breeds and, to a lesser extent, native breeds which have a degree of resistance to the disease. The study aimed to determine the prevalence of T. annulata infection in cattle in the arid and semi-arid regions of Algeria using serological and molecular methods. Bovine blood was tested for the presence of T. annulata-specific antibodies using the immunofluorescent antibody test (IFAT) and for parasite DNA using a polymerase chain reaction (PCR) for the gene encoding the major merozoite/piroplasm surface protein (Tams1). One hundred and sixteen individuals were screened and overall prevalences of 50.0 ± 4.6 % (IFAT) and 64.7 ± 4.4 % (PCR) were determined. There was moderate agreement between IFAT and PCR tests for the diagnosis of TT, with a sensitivity of 74.6 % and a specificity of 95.1 % for IFAT when compared against the PCR. Potential risk factors identified in this study were breed (OR = 2.25, 95% CI: 1.07–5.07), season of sampling (OR = 4.29, 95% CI: 1.97–10.9) and breeding system (OR = 8.60, 95% CI: 1.41–57.6). Sequence analysis of Tams1 PCR amplicons revealed 97.5–100% identity with one another and, overall, they were found to bear similarity to previously sequenced isolates from North Africa, Europe and Asia.